2011
DOI: 10.1002/glia.21229
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 deficiency potentiates methamphetamine‐induced dopaminergic axonal damage and gliosis in the striatum

Abstract: Oxidative stress that correlates with damage to nigrostriatal dopaminergic neurons and reactive gliosis in the basal ganglia is a hallmark of methamphetamine (METH) toxicity. In this study, we analyzed the protective role of the transcription factor Nrf2 (nuclear factor‐erythroid 2‐related factor 2), a master regulator of redox homeostasis, in METH‐induced neurotoxicity. We found that Nrf2 deficiency exacerbated METH‐induced damage to dopamine neurons, shown by an increase in loss of tyrosine hydroxylase (TH)‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 48 publications
4
53
0
1
Order By: Relevance
“…The present study showed that METH significantly increased the degradation of IjBa and increased the translocation of the p65 protein into the nucleus in glioma cells after exposure for different lengths of time and was associated with a remarkable increased in iNOS expression and NO production indicating that METH-induced inflammation mediated by NF-jB signaling. These results correlated well with earlier studies demonstrating significant activation of NF-jB signaling following METH treatment in both neuronal and glial cells [33,41]. In addition, we further observed the suppression of Nrf2 signaling pathway by METH in glioma cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study showed that METH significantly increased the degradation of IjBa and increased the translocation of the p65 protein into the nucleus in glioma cells after exposure for different lengths of time and was associated with a remarkable increased in iNOS expression and NO production indicating that METH-induced inflammation mediated by NF-jB signaling. These results correlated well with earlier studies demonstrating significant activation of NF-jB signaling following METH treatment in both neuronal and glial cells [33,41]. In addition, we further observed the suppression of Nrf2 signaling pathway by METH in glioma cells.…”
Section: Discussionsupporting
confidence: 93%
“…We next evaluated whether METH-reduced the activity of the Nrf2 pathway in glial cells, which is a typical mechanism of phase II enzymes that scavenge ROS [41]. It is well known that antioxidant genes, including HO-1, NQO-1, and c-GCLC, are transcribed by Nrf2, a major transcription factor regulating antioxidant response element (ARE)-driven phase II gene expression.…”
Section: Meth Induced Inflammation By Downregulating the Activation Omentioning
confidence: 99%
“…A large body of evidence indicates that the molecular mechanisms of terminal degeneration are separate and distinct from those of neuron somatic degeneration (Burke and O'Malley, 2012;Coleman, 2005;Raff et al, 2002;Ries et al, 2008). This idea is further supported by the fact that genetic inactivation of Nrf2 potentiates dopamine terminal loss without affecting survival of dopamine neurons in the SNpc (Granado et al, 2011b). In line with this, we observe no significant differences between the effects of single high dose and multiple lower doses on methamphetamineinduced dopaminergic neuronal loss, despite the clear dose dependence of dopamine terminal loss in the striatum.…”
Section: Discussionsupporting
confidence: 82%
“…Here, the striatal Nrf-2 expression was not modified by MTZ exposure. We did not expect this result since several studies, mainly related to Parkinson disease models, have demonstrated that this transcription factor in the striatum and/or dopaminergic neurons can be modulated by different drugs, including methamphetamine, 6-hydroxydopamine and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridinium (MPTP) [81,82]. The results obtained here indicate that the pattern of gene expression in response to hypothyroidism is complex and depends on the brain region considered.…”
Section: Discussionmentioning
confidence: 99%